The middle income trap from a Schumpeterian perspective. - Aghion,Philippe (Economics working papers., 2017)
Growth and development come from structural transformation, defined as the interplay between changes in economic structure and supporting institutions at different stages of development. The paper discusses how firms, competition, and institutions affect structural transformation.